Membangun Brand Image Melalui Penggunaan Augmented Reality: Meningkatkan Purchase Intention dengan Teknologi Canggih - Muhlisin; Wicaksana, Roziyan Adi (Jurnal Ilmu Manajemen, 2025)
This research aims to optimise the role of Augmented Reality (AR) by investigating how interactivity and vividness influence brand image and consumer purchase intention. Adopting a quantitative approach, data were gathered through an online questionnaire distributed to 130 respondents selected via purposive sampling, based on age classifications aligned with digital consumption trends from Katadata.id. The constructs were measured using a 5-point Likert scale and analysed using Partial Least Squares-Structural Equation Modelling (PLS-SEM) with SmartPLS software, which is well-suited for evaluating complex relationships in small to medium-sized samples. The findings indicate that vividness significantly influences purchase intention and positively affects brand image. Additionally, purchase intention is found to have a strong impact on brand image. The novelty of this study lies in its application of AR technology to explore its perceptual impact on branding, highlighting the pivotal role of visual interactivity. These insights underscore the importance of incorporating vivid and interactive AR features in digital marketing strategies. The research contributes to the growing literature on immersive technologies in consumer behaviour and offers practical implications for e-commerce firms aiming to enhance brand perception and drive conversions in a competitive digital marketplace.